Major bleeding risk assessment in atrial fibrillation patients taking vitamin K antagonists - Pivatto Júnior, Fernando; da Silva, André Luís Ferreira; Bezerra, Indira Valente; Pires, Leonardo Martins; Amon, Luís Carlos; Blaya, Marina Bergamini; Scheffel, Rafael Selbach (Clinical and Biomedical Research, 2015)
Background. The use of risk scores for the assessment of major bleeding and stroke in patients with atrial fibrillation (AF) helps evaluate the risks and benefits of oral anticoagulation therapy. The aim of this study was to describe the percentage of patients receiving anticoagulants for non-valvular AF with a high risk of major bleeding based on the HAS-BLED score, as well as identify potential modifiable risk factors of bleeding and compare the risk of major bleeding with the risk of stroke. Methods. Retrospective cohort study involving patients of the anticoagulation outpatient clinic of the Division of Internal Medicine at Hospital de Clínicas de Porto Alegre. Major bleeding risk was estimated based on the HAS-BLED score and stroke risk was determined using the CHADS2 and CHA2DS2-VASc scores. Results. Sixty-three patients were investigated (mean age 74.3±10.9 years). The median HAS-BLED score was 2 points, 19 (30.2%) patients had a score ≥ 3 (high risk). The most prevalent modifiable risk factors were labile TP/INR (36.5%) and concomitant use of drugs (30.2%). The absolute risk of major bleeding based on the HAS-BLED score was higher than the risk of stroke in three (4.8%) and four (6.3%) patients in comparison with the CHADS2 and CHA2DS2-VASc score, respectively. Conclusions. We concluded that the percentage of patients with high risk of major bleeding is similar to the rate found in the national literature (30.2%). In addition, the most prevalent modifiable risk factors in our cohort were labile TP/INR and concomitant drug use.